Factors Influencing Homestay Performance: An Empirical Analysis Using TOE Framework - NURUL LIYANA RAMLAN (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Despite being a part of Malaysia's tourism sector for many years, homestay is still not as popular as other travel-related services. Thus, the aim of this research is to determine the factors that homestay ought to have in order to enhance their performance and put them on level with other tourism offerings. The purpose of this study is to examine how the TOE Framework can enhance homestay performance. A self-administered questionnaire was given to 30 homestay operators in Sabah and Sarawak in order to accomplish the goal and the result were analysed using SPSS software. All three variables (technology factors, organization factors and environment factors) tested in this research on the performance of homestay were found to be significant. The results indicate that in order to enhance their performance and maintain their competitiveness in the tourism sector, homestay should prioritize all of these factors. The originality of this study has provided essential information for decision-makers who are involved in the implementation for future research, assisting the creation of the most productive homestay business plan and providing empirical data for this research.